Antibiotic procurement and ABC analysis for a comprehensive primary health care clinic in the Eastern Cape province, South Africa - Sharma, Samridhi; Tandlich, Roman; Docrat, Mohamed; Srinivas, Sunitha (Southern African journal of infectious diseases, 2020)
Antimicrobial resistance (AMR), a major threat to global public health, can be addressed using a managed care approach. This includes timely analysis of antibiotic consumption and procurement data to drive evidence-based policies and practices in healthcare facilities. 'ABC analysis' presents an opportunity for this. ABC analysis data for a comprehensive Primary Health Care (PHC) clinic in the Eastern Cape province of South Africa was obtained from the Provincial Department of Health for 01 April 2015 to 31 March 2018. Procured antibiotics were analysed on the quantities purchased, total cost, route of administration and spectrum of activity. Antibiotic categorization was also carried out according to the (WHO EML) 2017. Antibiotics made up approximately 7% of the total annual pharmaceutical expenditure. A total of 31, 35 and 34 antibiotics were procured in the first, second and third years, respectively. The most procured antibiotics were: (1) isoniazid, (2) flucloxacillin, (3) azithromycin, (4) a combination of rifampicin, isoniazid, pyrazinamide, and ethambutol and (5) amoxicillin. Overall, 55%, 2% and 15% of antibiotics accounted for the 'Access', 'Watch' and 'Access and Watch' categories, respectively, of the WHO EML. No 'Reserve' antibiotics were procured. The remaining 28% were antituberculosis medicines. Altogether, 89%, 8% and 3% of the antibiotics were respectively administered orally, systemically, and topically. A total of 58% were broad-spectrum and 42% were narrow-spectrum antibiotics. Oral antibiotics in the 'Access' category presented favourable usage of antibiotics. Decreasing the use of broad-spectrum antibiotics requires consideration.